Comparative evaluation of flavor compounds in fermented green and roasted coffee beans by solid phase microextraction‐gas chromatography/mass spectrometry. (10th July 2019) - Kim, Su‐Jin; Lee, Sul; Bang, Eunjung; Lee, Sunho; Rhee, Jin‐Kyu; Na, Yun‐Cheol
Abstract: Specific fermentation processes such as digestive bioprocessing and monsooning have been of interest to coffee consumers. Volatile compounds of beans during the different fermentation processes vary considerably and exhibit different profiles. The representative flavor compounds for the luwak green bean were found to be pentamethyl heptane and 3‐methyl‐1‐butanol, while more diverse and distinct compounds were observed from the monsooned green bean, namely alkyl butanals, pinenes, benzaldehyde and butanediols. However, after roasting, the fermented form of both beans contained similar types of volatiles and their relative contents compared to those of non‐fermented roasted beans, except for α‐pinene in luwak and 2‐methyl furan in monsooned beans. In principal components analysis and partial least squares‐discriminant analysis (PLS‐DA), the different fermented beans were clearly distinguished by the extracted peak entities from their total ion chromatograms. The s‐plot and variable importance on projection (VIP) values related to PLS‐DA showed the significant compounds contributing to the identification of the groups. 3‐Methyl‐1‐butanol was the most distinctive compound for the luwak green bean, and β‐pinene, ethylbenzene and benzaldehyde were found to be the significant compounds in the monsooned green bean. In roasted beans, the most significant compounds to distinguish luwak were furfural, α‐pinene and 3‐carene with high variable in the projection (VIP) values. A significant presence of pyrazine, alkyl pyrazines, pyridine and alkyl pyridines contributed to differentiating both fermented roasted coffee beans from the unfermented roasted beans. Abstract : The headspace SPME method coupled with GC/MS was employed to identify volatiles from green and roasted beans of luwak and monsooned coffee. The exploratory data analysis (PCA and PLS‐DA) were applied to discover intricate and delicate compounds available as candidate markers for differentiating the fermented coffee beans. This method provided a tool for evaluating coffee quality or authenticity depending on the fermented type of beans.